NATURAL TYPE IA DIAMOND WITH GREEN-YELLOW COLOR DUE TO Ni-RELATED DEFECTS - Wang W.; Hall M.; Breeding C.M. (My University, 2007)
Commonly seen in HPHT-grown synthetic diamonds with a green component, nickel-related defects were identified for the first time in a type la natural diamond with a strong green component. The 1.75 ct Fancy green-yellow diamond showed a strong peak at 1332 cm-1 in the IR absorption spectrum, strong absorption from the 1.40 eV center and the associated ∼685 nm band in the Vis-NIR spectrum, and extremely strong emissions from Ni-related defects in the photoluminescence spectra - all of which proved that nickel was the primary cause of the green color.